Medicine and society - Della Giustina, Tatiana Bragança de Azevedo (Revista Bioética, 2020)
Although the first concerns about bioethics took place after the Great Wars, especially after World War II, this field of research only took its current shape in the 1970s. In times of social change, bioethical principlism has a lot to contribute to science and the humanities 1.